Reduction of Starting Current Surge in Single-Phase Induction Motor Using Arduino Nano - Silvi Nur Rakhman Nisa; Ibrohim Ibrohim; Tri Rijano; Subuh Isnur Haryudo (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2026)
Single-phase induction motors experience high inrush current during the starting process, which can degrade power quality and accelerate electrical component deterioration. This research aims to design and evaluate an Arduino Nano–based soft starter system for a single-phase induction motor to limit the starting current. The proposed method employs stepwise series resistance control using relay modules driven by the Arduino Nano, while electrical parameters including voltage, current, and power are monitored in real time using a PZEM-004T sensor. Experimental tests were conducted by comparing the motor starting current before and after the implementation of the soft starter under several operating conditions. The results demonstrate that the proposed system is able to reduce the starting current by 15%–20% compared to direct-on-line operation, with stable and consistent current reduction characteristics. The analysis indicates that the current limitation effectively reduces electrical stress on the motor without adversely affecting the acceleration process. It can be concluded that the developed soft starter system successfully meets the research objectives and is suitable as a simple and cost-effective solution for controlling the starting current of single-phase induction motors.